"Give us this day our daily bread" - clergy's lived religion in Pretoria central areas - M. Rabe; C. Lombaard (Acta Theologica)
The aim of this article is to reflect on how clergy, working in Pretoria central areas, live out (the external dimension) and experience (the internal dimension) their faith in their everyday life. Thirteen clergy were briefly interviewed on an individual basis and then asked to keep a diary for two months. Four of the interviewed clergy completed the diary project. Based on the interviews and the diaries, the main themes that could be identified in relation to faith in their everyday lives, are responding to the challenges associated with urban ministry, including poverty and trauma, and dealing with the sometimes overwhelming experience of stress that the demands of this ministry can create. Distancing from the different aspects of their tasks, attending to personal needs, and focusing on individual experiences of faith are the main identified strategies the participants employ in dealing with the daily pressures they are exposed to.